Private Solutions for Infrastructure : Opportunities for Uganda - Public-Private Infrastructure Advisory Facility (Washington, DC: World Bank, 2013)
This Country Framework Report for Uganda, is part of a series focused on achieving poverty eradication, rural development, and economic growth through sustained infrastructure programs. Introducing private investment to the infrastructure sectors, lies at the heart of the Government's strategy to achieve combined sector restructuring, and liberalization. To this end, infrastructure development must be responsive to economic, and social needs, based on clear planning, and policy coordination. The report prioritizes on exploiting all beneficial options for private sector involvement, paying close attention to the development of effective incentive frameworks. Moreover, subsidy and donor funding mechanisms should be introduced to support poverty alleviation in the context of reform, while measures should be taken to ensure capacity is available to execute the reform program effectively, and provide for its coordination to maximize economic development. There should be a strong bias toward sector liberalization, except where this would result in significant loss of economies of scale, or scope, and, the establishment of an overall regulatory environment, attractive to private sector participation should be a critical priority, while protecting the interests of consumers.